2022
DOI: 10.3390/s23010112
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-Sensitive Patterning of Azopolymer Thin Films Using Multiple Structured Laser Beams

Abstract: The polarization sensitivity of azopolymers is well known. Therefore, these materials are actively used in many applications of photonics. Recently, the unique possibilities of processing such materials using a structured laser beam were demonstrated, which revealed the key role of the distribution of polarization and the longitudinal component of light in determining the shape of the nano- and microstructures formed on the surfaces of thin azopolymer films. Here, we present numerical and experimental results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…In optical data transmission, the results obtained can increase the signal power when the data are encoded in light beams by their polarization, and then the incoming beams are identified by polarizers [ 39 , 40 ]. In addition, the obtained results can be used for processing polarization-sensitive materials [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In optical data transmission, the results obtained can increase the signal power when the data are encoded in light beams by their polarization, and then the incoming beams are identified by polarizers [ 39 , 40 ]. In addition, the obtained results can be used for processing polarization-sensitive materials [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polarizing filters make it possible to encode information into incoming light and decode the information using photosensitive materials such as azopolymers. Q-plates are useful for producing linearly polarized laser beams with a variety of polarization orientations, allowing for simultaneous, non-uniform laser patterning of thin azopolymer films [114].…”
Section: Creation Of Structured Beams By Spiral Mass Transportmentioning
confidence: 99%
“…It was previously shown that using two or more interfering beams with specified properties, one can quickly form two-dimensional or three-dimensional diffraction structures in photosensitive materials [14][15][16][17][18][19][20]. Moreover, studies of the influence of the polarization state of various beams on the formation of relief in polarization-sensitive materials are increasingly appearing [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%